A Case Report of Non-puerperal Uterine Inversion due to Submucosa Leiomyoma in a Young Virgin Woman. (16th August 2022) - Moshayedi, Faezeh; Seidaei, Hengameh Sadat; Salehi, Amir Mohammad
Abstract : The inversion of the uterus is a rare complication of the puerperium and much rarer during the non-puerperal period. The most common cause of non-puerperal inversion is a submucosa leiomyoma; however, identification can be difficult. Herein, we present a case of pedunculated uterine leiomyoma that causes uterus inversion in a 30-year-old virgin woman with a correct diagnosis; a hysterectomy was prevented for the patient.